2008
DOI: 10.1007/s11483-008-9074-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Barrier Properties of Avenin, Kafirin, and Zein Films

Abstract: Biodegradable and renewable materials can be manufactured from prolamins, which are the major storage protein fraction of cereals. This paper investigates the material properties of oat prolamin (avenin), corn prolamin (zein), and sorghum prolamin (kafirin). Glass transition temperature, dry solid content, stress at break, strain at break, oxygen permeability, and water vapor permeability were analyzed at different plasticizer contents. Avenin was plasticized with glycerol, and kafirin and zein were plasticize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…At low plasticizer concentration, sorbitol led to a higher ultimate tensile strength than glycerol and mannitol. Gillgren et al [238] added polyethylene glycol, glycerol and lactic acid in different concentrations to kafirin, zein and avenin. In particular, zein was more stretchable at higher plasticizer contents [232] compared to zein films prepared in aqueous ethanol or acetone containing no plasticizer, glycerol or glycerol/poly(propylene glycol) (1:3 ratio).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…At low plasticizer concentration, sorbitol led to a higher ultimate tensile strength than glycerol and mannitol. Gillgren et al [238] added polyethylene glycol, glycerol and lactic acid in different concentrations to kafirin, zein and avenin. In particular, zein was more stretchable at higher plasticizer contents [232] compared to zein films prepared in aqueous ethanol or acetone containing no plasticizer, glycerol or glycerol/poly(propylene glycol) (1:3 ratio).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Even though collagen and gelatin coatings were reported to both effectively retain water in meat products (Antoniewski et al, 2007;Farouk et al, 1990), extensive moisture loss of kafirin coated pears compared to the uncoated product left them unacceptable toward consumers . The authors ) therefore suggested to prepare wax or triglycerides/kafirin mixtures instead of pure kafirin coatings to prevent moisture loss as kafirin films themselves do not function effectively as water barriers (Emmambux et al, 2004;Gillgren & Stading, 2008). Because lipids form a very suitable moisture barrier as a result of their hydrophobic character, lipophilized proteins possibly form more effective coatings for fruit.…”
Section: Shelf Lifementioning
confidence: 99%
“…Kafirin showed equal WVP at all plasticizer contents, as did zein at 20% and 30%, but higher at 40% (3.6 vs 2.5 gmm/m²h kPa). 4 A conclusion to be made about barrier properties is that, while the polarity of the plasticizer (hydrophilic or hydrophobic) and the plasticizer content are important, the microstructure also has an impact on the permeability. Error bars indicate the scatter as the 95% confidence interval Cavities, holes, or irregular and heterogeneous structure increase the gas permeability.…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…3 Until now studies have focused principally on prolamins such as avenin, kafirin, zein, and gliadin. [4][5][6][7] This study, however, focuses on pennisetin, the prolamin from pearl millet (Pennisetum glaucum). Pearl millet is cultivated for T. Gillgren : M.-V. Faye : M. Stading its edible seeds, consumed by humans and animals.…”
Section: Introductionmentioning
confidence: 99%